Design Optimization of a Modern Catamaran Using Dynamic Stability Criteria for Improved Safety in Jeneberang River Transport - Muh Yusril Syam (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
River transportation in Sungai Jeneberang plays a vital role in supporting daily mobility between Kabupaten Gowa and Kota Makassar. However, the existing traditional vessels (katinting) exhibit low safety standards due to poor stability and the absence of adequate safety equipment. This study aims to optimize the design of a modern catamaran based on dynamic stability criteria to improve river transport safety. The research applies a Parent Design Approach combined with geometric modeling using AutoCAD and stability analysis using Maxsurf. The design process is based on field data and evaluated under three loading conditions: lightship, half load, and full load. The resulting principal dimensions are LOA = 12,00 m, B = 5,00 m, T = 0,55 m, with ratios L/B = 2,4, B/T = 9,09, and H/T = 2,91, indicating favorable stability characteristics. The results show that all loading conditions meet the IMO Intact Stability Code (IS Code) requirements, with positive metacentric height (GM) and stable righting arm (GZ) curves. The final 3D design accommodates 20 passengers, 15 motorcycles, and safety equipment, ensuring improved operational safety and comfort. This study contributes to the development of small-scale river transport design by integrating empirical data with stability-based optimization, offering a practical and safer alternative for sustainable river transportation systems.